New records of three species of the genus Aricia Reichenbach, 1817 (Lepidoptera: Lycaenidae) in Croatia - Koren, Toni (Acta entomologica slovenica (Ljubljana), 2012)
Among four species of the genus Aricia Reichenbach 1817 that inhabit the territory of Croatia, three can be regarded as mountain species: Aricia anteros (Freyer, 1838), Aricia artaxerxes (Fabricius, 1793) and Aricia eumedon(Esper, 1780). For all three species only a limited number of records exist, with large distribution gaps between them. New records for all three species from the Dinarids are presented. The most notable are two records of A. anteros, which was confirmed for Croatia after a period of more than 60 years. Its known range of occurrence in Croatia was greatly expanded with the records on two new localities outside Velebit Mts.
Keywords: Aricia artaxerxes; Aricia eumedon; Dinaridi; Dinarids; Lepidoptera; Lycaenidae; metulji; new records; nove najdbe